2018
DOI: 10.31413/nativa.v6i6.7039
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF SALICYLIC ACID ON SOME OF MORPHOLOGICAL AND PHYSIOLOGICAL TRAITS OF WHEAT (Triticum aestivum L.) UNDER DIFFERENT LEVELS OF CADMIUM STRESS

Abstract: Nowadays, salicylic acid is used as a growth regulator to reduce the negative effects of different levels of stress. This research was conducted as factorial experiment on a completely randomized block design. Wheat plants were planted in four levels of cadmium (0, 100, 200 and 300 μmol) with three levels of salicylic acid (0, 0.5 and 1.0 mmol) in three replications. The results showed that root heights, fresh and dry weight of the stem were decreased significantly, and leaf proline and catalase and superoxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Saheri et al, (2020) found that foliar spraying of SA of common purslane plants under drought stress resulted with increase in length, fresh weight and dry weight. Foliar spraying of SA caused increase in shoot and root length and shoot fresh and dry weight of wheat seedlings in greenhouse (Behnam et al, 2018). It was reported that shoot and root fresh mass of 15 days old wheat plants growth from seeds soaked with SA was weightier than control (Loutfy et al, 2020).…”
Section: Physiological Parametersmentioning
confidence: 97%
“…Saheri et al, (2020) found that foliar spraying of SA of common purslane plants under drought stress resulted with increase in length, fresh weight and dry weight. Foliar spraying of SA caused increase in shoot and root length and shoot fresh and dry weight of wheat seedlings in greenhouse (Behnam et al, 2018). It was reported that shoot and root fresh mass of 15 days old wheat plants growth from seeds soaked with SA was weightier than control (Loutfy et al, 2020).…”
Section: Physiological Parametersmentioning
confidence: 97%
“…Thus, the attenuating effect of SA under drought conditions may be associated with its role in photosynthesis [22,23] and in stomatal regulation [24], which, in turn, act as pathways eliminating reactive oxygen species and providing protection to the photosynthetic apparatus under stress conditions [25,26].…”
Section: Introductionmentioning
confidence: 99%